Analysis of Students' Critical Thinking Skills Based Project Based Learning Model in the Merdeka Curriculum - Suharti, Suharti; Lukman, Lukman; Yamin, Muhammad; Faidin, Faidin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Critical Thinking is a 21st century skill that includes critical thinking, creativity, communication, and collaboration. In the Merdeka curriculum, it influences the improvement of students' ability to find information and interpret texts, analyze, evaluate and draw conclusions presented in local wisdom based history learning, so that in the end students can compile projects in the form of papers. The study aims to analyze the use of history learning of local wisdom -based PjBL to improve students' critical thinking skills in the Merdeka curriculum. The approach used in this study is a quantitative approach with a descriptive research type. This approach describes variables as they are with data in the form of numbers, which are then interpreted. The instrument uses test, observation and questionnaires. The sample used was an applied science class of 4 people and an applied social science class of 4 people. The study shows that the results of the critical thinking skills of the two classes have different achievement categories. Applied Science Class with Very Good Category 95 and Quite Good 75-77, while Applied Social Studies Class has a Very Good category with a score of 95 and Good with a score of 90.